Analisis Citra Digital Sederhana untuk Kuantifikasi Kerusakan Mekanis Buah Pisang Setelah Simulasi Transportasi - Wahyu Hidayat; Cicih Sugianti (abe.fp.unila.ac.id, 2026)
Bruising is a common form of mechanical damage occurring in bananas during transport that can reduce fruit quality. This study aimed to determine the optimal threshold for measuring banana bruise areas using digital image analysis and to evaluate the effects of vibration frequency and duration on bruise development during storage. The percentage of bruised area was derived from image segmentation using ImageJ at threshold values of 120, 130, 140, 150, and 160. The optimal threshold was selected using Principal Component Analysis (PCA), while treatment effects were analyzed using analysis of variance (ANOVA) and Duncan’s post-hoc test. PCA results indicated that all thresholds were strongly correlated and represented similar information; consequently, a threshold of 150 was selected as the best option based on statistical results and visual evaluation of the segmentation. ANOVA results showed that the interaction between vibration frequency and duration had a highly significant effect on the percentage of bruised area, whereas duration alone did not have a significant effect. Duncan’s test revealed that the 10 Hz–60 minute combination resulted in the lowest percentage of bruised area, while the 30 Hz–60 minute combination resulted in the highest. This study demonstrates that a threshold of 150 can serve as a basis for quantifying banana bruising and that the extent of bruising during transport simulation is influenced by the combination of vibration frequency and duration.